Educational experiences for Elementary School students learning about the characteristics and importance of insects (Research, Society and Development, 2025)
This study objective to evaluate whether using alternative educational practices increases students knowledge using the topic "The importance of insects in the environment" as an example. The study was conducted in two 5th grade classes of a public school in Teixeira de Freitas, state of Bahia, Brazil, from May to September 2016. To verify the effectiveness of the practices carried out, a questionnaire was used to evaluate the perceptions of the students on the topic addressed before and after the implementation of the educational activities. The data obtained from the questionnaire (before and after the activities) was subjected to frequency analysis and was compared using a test of proportions (binomial test) at P < 0.05. In general, it was found that before the interventions, students knew little about the scientific and ecological importance of insects, could not effectively distinguish them from other arthropods and animal classes, and often held negative beliefs about these organisms. However, after the interventions, the students' ability to recognize insects, as well as their concepts and behaviors related to insects, changed significantly. The results demonstrate the effectiveness and importance of alternative teaching methods that allow students to have more contact with the subject matter. Also, how significant is to make them active subjects in the teaching-learning process, facilitating the construction of knowledge.